Analisis Manajemen Strategi terhadap Kinerja Usaha Kecil dan Dampaknya Bagi Kesejahteraan Masyarakat Usaha Kecil di Mojokerto - Wiwik Retnaningsih (Jurnal Aplikasi Manajemen, 2012)
The purpose of this research is finding out which factors that influence small working performance. The detail purpose of this research is analyzing the influence of internal and external factors to performance, market segment access to performance, capital resource access to performance, capability to performance, management access to performance, technological access to performance, business vision to performance, guidance to performance, government regulation to performance.Location of this research is Mojokerto City and Regency. The main instrument that used in this research to collect data is questionnaire through structured interview technique by using 5 point Likert scale. Moreover, primary data that collected through questionnaire is also accompanied by interview with officers of Industry and Commerce Department. Secondary data is collected from Industry and Commerce Department. The result of this research shows : Internal and external factor influence small work performance in Mojokerto City and Regency. Partially, five variables that is capital resource access, management, market segment access and government regulation have positive and significant influence to financial performance; management, market segment access and critical awareness have positive and significant influence to customer performance; capability, guidance and critical awareness have positive and significant influence to internal performance; management, market segment access and critical awareness have positive and significant influence to learning and growth performance.Keywords: Internal factor; external factor; performance and prosperity